1985
DOI: 10.1200/jco.1985.3.12.1624
|View full text |Cite
|
Sign up to set email alerts
|

A controlled evaluation of recent approaches to biochemical modulation or enhancement of 5-fluorouracil therapy in colorectal carcinoma.

Abstract: Three hundred thirty-five previously untreated patients with advanced colorectal carcinoma were randomly assigned to treatment with 5-fluorouracil (5-FU) alone, 5-FU plus N-(phosphonacetyl)-L-aspartic acid (PALA), 5-FU plus high-dose thymidine, 5-FU plus levamisole, or 5-FU plus methyl CCNU, vincristine, and streptozotocin (MOF-Strept). Dosages were designed to produce definite toxicity in the majority of patients, although the nature of dose-limiting reactions varied considerably among regimens. 5-FU alone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The most effective single agent is 5-fluorouracil, with a 20% response rate; and randomised trials have not yet shown any benefit for combination chemotherapy (Buroker et al, 1985). The major metabolite of 5-fluorouracil is a potent inhibitor of thymidylate synthetase, though whether this is the principal mode of cytotoxicity remains to be established (Benz & Cadman, 1981).…”
mentioning
confidence: 99%
“…The most effective single agent is 5-fluorouracil, with a 20% response rate; and randomised trials have not yet shown any benefit for combination chemotherapy (Buroker et al, 1985). The major metabolite of 5-fluorouracil is a potent inhibitor of thymidylate synthetase, though whether this is the principal mode of cytotoxicity remains to be established (Benz & Cadman, 1981).…”
mentioning
confidence: 99%
“…There was a statistical difference in complete response rates between group 1 (31%) and group 2 (47%), (0.02<P<0.05) and a statistically significant reduction was observed in the incidence of toxic cycles (>grade 2, group 1= 20% versus group 2 = 12.4%; 0.02 <P <0.05). Pharmacokinetic follow-up of these patients has proved to be an objective means to improve therapeutic index significantly.In addition to the digestive tract, where its efficacy remains limited (Buroker et al, 1985), chemotherapy by 5-FU is used for other disease sites. In squamous cell carcinoma of the head and neck very high response rates have been observed when the drug is combined with cisplatin (CDDP) (Thyss et al, 1986b;Amrein & Weitzman, 1985;Kish et al, 1982).…”
mentioning
confidence: 99%
“…In addition to the digestive tract, where its efficacy remains limited (Buroker et al, 1985), chemotherapy by 5-FU is used for other disease sites. In squamous cell carcinoma of the head and neck very high response rates have been observed when the drug is combined with cisplatin (CDDP) (Thyss et al, 1986b;Amrein & Weitzman, 1985;Kish et al, 1982).…”
mentioning
confidence: 99%
“…In addition, the combination of LEV with 5-FU in advanced colon cancer was shown not to be superior to 5-FU single-agent therapy (Buroker et al, 1985). At the time the present study was initiated, combination of LEV and 5-FU was considered to be standard therapy to eliminate minimal residual disease.…”
mentioning
confidence: 84%